Sosialisasi Terapi Swamedikasi Akupresur Dan Inhalasi Minyak Wangi Untuk Mengurangi Gejala Pilek Pada Siswa SDN 02 Terong Tawah - Setyowati, Kirana Ayu; Widyasari, Ni Luh Ayu Sri; Salam, Mahra Murniati; Fitri, Maulida Khalila; Yustitia, Nur Tahany; Pratiwi, Eskarani Tri (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Abstract: Upper Respiratory Tract Infection (URTI) or common cold is an acute viral infection that is temporary in nature in the upper respiratory tract, which can also involve the lower respiratory tract. The common cold, which is a combination of typical symptoms, is a common illness that can disrupt activities such as work and school. Children are particularly vulnerable to catching colds due to not having immunity to many viruses, poor personal hygiene, and frequent close contact with other children infected with these viruses. Acupressure is a self-medication technique or treatment involving massage or pressure on the skin surface. Meanwhile, inhalation therapy is a therapy involving the direct delivery of medication to the lungs. The purpose of this community service activity is to increase early knowledge and understanding of self-medication methods for colds using acupressure and aromatherapy inhalation to reduce cold symptoms in students at SDN 02 Terong Tawah. The method of community service activities is using pretest and posttest questionnaires. The results of the community service activity are measured using the One Group Pretest Posttest Design method. Keywords: Cold, URTI, Acupressure, Inhalation Therapy, Self-Medication